Flaviviral disease mosquito vector surveillance in Incheon Metropolitan City and the Hwaseong area, Gyeonggi‐Do, Republic of Korea, in 2015. Issue 1 (26th January 2020) - Bahk, Young Yil; Jun, Hojong; Jegal, Seung; Kim‐Jeon, Myung‐Deok; Roh, Jong Yul; Lee, Wook‐Gyo; Park, Seo Hye; Ahn, Seong Kyu; Lee, Jinyoung; Gong, Young Woo; Kwon, Mun Ju; Kim, Tong‐Soo
Abstract: Owing to global climate change, the global resurgence of vector‐borne infectious diseases and their potential to inflict widespread casualties among human populations has emerged as a pivotal burden on public health systems. In this study, the prevalence of flaviviral diseases transmitted by mosquitoes, and their target vector diversity, abundance, and distribution was investigated to enable the mapping of hotspots for these diseases. For the surveillance of the vector mosquitoes carrying flaviviruses during April to November 2015, female mosquitoes were collected to study whether they carried pathogens from abroad at seven locations in Incheon Metropolitan City (Incheon) as a typical urban area and Hwaseong‐si (= city, Hwaseong) of Gyeonggi‐do (= province) as a rural area. A total of 15 species belonging to seven genera (29, 102 female mosquitoes) were collected with black‐light and BG‐Sentinel™ traps at a collection rate of 260 per trap/night from whole collection locations. The most collected mosquito species in Incheon were Aedes vexans nipponii (species ratio (SR), 29.9%) and the Culex pipiens complex (SR, 28.8%), followed by Anopheles sinensis s.l . (SR, 27.9%) and Ochlerotatus koreicus (SR, 7.1%). From the results of viral RNA detection, five flaviviruses were found in 20, 981 individuals (excluding An. sinensis ; 696 pools) in the Cx. pipiens complex and Ae. vexans nipponii . Three Japanese encephalitis virus (JEV)‐positive pools were from the Cx. pipiens complex, a Chaoyang virus pool was found from Ae. vexans nipponii, and the remaining unidentified flavivirus pool was from Cx. pipiens . The three JEV‐positive pools were phylogenetically grouped as genotype V. The results of our study demonstrate that enhanced monitoring and long‐term surveillance of these vector viruses are of great public health importance.